Non-linear 3D finite element analysis of full-arch implant-supported fixed dentures - Ferreira, Mayara B. [UNESP]; Barao, Valentim A.; Delben, Juliana A. [UNESP]; Faverani, Leonardo P. [UNESP]; Hipolito, Ana Carolina [UNESP]; Assunção, Wirley Goncalves [UNESP] (Elsevier B.V., 2014)
Despite the necessity for faster clinical protocols for immediate loading of implant-supported dentures, there is a lack of biomechanical studies to confirm the rigid splinting effectiveness. We compared the stress in mandibular full-arch implant-supported fixed dentures under immediate loading through three-dimensional finite element analysis. Edentulous human mandible models were restored with a 4-implant fixed denture. Implants were splinted with a metallic framework and submitted to conventional loading (group A-control), with acrylic resin and submitted to immediate loading (group B), with a metallic framework and submitted to immediate loading (group C), and with acrylic resin and a prefabricated distal bar and submitted to immediate loading (group D). Models were supported by masticatory muscles. A 100-N oblique load was applied on the first molar. Group A presented the lowest stress and implant displacement values, whereas group D showed the highest values. In bone, groups under immediate loading exhibited the highest stress, whereas the group experiencing conventional loading showed an approximately 50% reduction. All groups submitted to immediate loading presented similar stress values in pen-implant bone. The loading protocol influenced the stress and implant displacement, but the design of the fixed denture did not affect the stress in the pen-implant bone. Rigid splinting of implants submitted to immediate loading is not essential for treatment success. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Dental implant; Biomechanics; Immediate loading; Computed tomography